Synthesis, Characterization and Kinetic Study of poly(vinyl acetate)-g-Chitosan and its Use in Removal of Cadmium (II) ions from Water - Hammood, Ali Jasim; Al-Ameri, Salam A H; Al-Qaisi, Zyad H Jawad (Al-Nahrain Journal of Science, 2019)
The grafted vinyl acetate copolymerization lying on chitosan in weak acidic aqueous solution was examined via using K2S2O8 as initiator. FTIR spectra, DSC, DTG and TGA were used for graft polymer characterizing. The monomer to chitosan ratio was tested and the optimal grafting conditions were affixed. the highest grafting percentage PG of production polymers have been applied to remove Cd(II) ions from water samples through adsorption experiments at pH=7. The amounts of adsorbed metal ion on the polymers was estimated using atomic absorption spectrophotometer. The temperature effect on Cd(II) adsorption was studied too. Langmuir and Freundlich isotherms as well as kinetic study equations were employed to fit the experimental data. The results of the adsorption equilibrium for Cd(II) fitted well to Langmuir isotherm and the removal percentage at 30°C after 5 min is 76.65 % and the thermodynamic parameters for the adsorption are ΔH= 96.87 kJ/mol ΔS= 339.19 J/mol K and ΔG= -5.11, -11.13 and -11.78 kJ/mol in different temperatures. The kinetic study of these adsorption isotherms showed that all these isotherms correlates well with the second order equation.